KAJIAN NORMATIF ATAS KEPAILITAN BUMN (PERSERO) DALAM KAITANNYA DENGAN PENGATURAN PERSEROAN TERBATAS - Dewi Tuti Muryati; B. Rini Heryanti; Dharu Triasih (Universitas Semarang, 2015)
Bankruptcy problem to Warm Up State Belonging Effort in praktik jurisdiction is still to be felt haven't available perception equation among practitioners sentences notably judges. On latterly there are many Effort Body Belongs To State notably get Persero's form that supplicated by bankrupt at Commerce Justice. Position Warms Up State Belonging Effort as body of civil law can as creditor and get too as debtor. If Effort Body Belongs To State have book debt and have maturity value but its book debt nonpayment, therefore bases UU No. 40 Years 2007 about limited liabilities and UU No. 37 Years 2004 about bankruptcy and Paying liabilities Pauses Book Debts therefore necessarily gets to be supplicated by bankrupts. But with marks sense arrangement about state wealth accompaniment in capital BUMN Persero who gets bearing with arrangement about state finance, therefore then evoking various opinion hits BUMN'S bankruptcy in particular that gets to form Persero. Based on on that condition, this research is done for menganalisis arrangement hits bankruptcy to BUMN Persero in its bearing with limited liability bankruptcy bases UU No. 37 Years 2004, effect law for the parties to bankrupt statement on BUMN Persero, and BUMN Persero's bankruptcy if concerned by state asset position in BUMN. Observational exterior target this is yielding scientific opus observational one be publicized on journal. Approximate methods who will be utilized deep observational it is normatif's judicial formality approaching. Ala does this research descriptive analytical, which is with give picture specially up on aught fact. Data collecting is done throughstudi bibliography and studi is document that as data of secondary and that dianalisis will kualitatif's ala. Based yielding observational acknowledged that deep Section 2 sentences (5 ) UU No. 37 Years 2004 just manage blurs only about bankruptcy BUMN which is just concerns BUMN that moving at public behalf area and not give detail's ala formulation, remembering terminological BUMN UU No. 19 Years 2003 is Perum and Persero. Hereafter been known that bankrupt statement application to BUMN Persero, will take in law effect to debtor and the parties which is available one needs dimintakan by particular party and given institution assent or Rule of Reason , but there is also that prevailing by that law, e.g. confiscate common. Known too that with publishes it Supreme Court letter No. WKMA / Yud / 20 / VIII / 2006 dates16th August 2006 and publish PP No. 33 Years 2006 is next to be followed Finance Minister statement which is corporate Credit managements States / Region is done bases UU limited liabilities and UU BUMN, thing such it if bankruptcy happening on BUMN Persero.